PHYSICAL ACTIVITY LEVELS AND THEIR RELATIONSHIP WITH ENERGY EXPENDITURE IN THE DAILY ACTIVITIES OF ADULT AND ELDERLY WOMEN IN THE CITY OF VIÇOSA (MINAS GERAIS/BRAZIL) (Fiep Bulletin - online, 2014)
Introduction: Modifications resulting from aging reduce elderly people's physical capacity and influence their daily energy expenditure. Objective: To describe daily physical activity levels among women, classifying them as "high", "medium" or "low" levels. Method: Seventy-five adult and elderly women (mean age: 66.04  6.55 years) enrolled in the Municipal Program for the Third Age, in Viçosa, Minas Gerais, agreed to participate. The International Physical Activity Questionnaire (IPAQ), short version, and a personal data questionnaire were applied, and weights (kg) and heights (cm) were measured to calculate the body mass index (BMI). Descriptive statistics were utilized; relationships between metabolic equivalent (MET), BMI and age group were verified using the simple linear regression test; and associations between categorical variables were analyzed using the chi-squared test, with p< 0.05. Results: The means and standard deviations of weight and height were 46.98  31.19 kg and 153.9  5.63 cm; 62.6% of the women received up to two minimum salaries and 70.6% had not completed elementary education. Most of them presented moderate (34.7%) or high (58.7%) energy expenditure, and 98.6% performed large quantities of domestic tasks. No significant relationship was found between BMI and MET, although the elderly women classified as having "low" physical activity levels presented high BMI. Ages were inversely related to MET values. There was no relationship between IPAQ and reported diseases, but most of the women with "high" and "moderate" IPAQ classifications presented at least one risk factor for coronary diseases. Conclusion: These women's incomes and schooling were equivalent to those found among the oldest segment of the general population, particularly among women. Although of low intensity, the large volume of domestic activities constitutes an important stimulus towards high energy expenditure, and this may be a protective factor against cardiovascular diseases and for maintaining the independence of this group.
Keywords: elderly people; physical activity; energy expenditure